2008
DOI: 10.1080/10919390802421267
|View full text |Cite
|
Sign up to set email alerts
|

Spam and Beyond: An Information-Economic Analysis of Unwanted Commercial Messages

Abstract: The phenomenon of unwanted commercial messages (UCM), including e-mail spam and emerging forms that target other Internet communications facilities, is analyzed from an information-economics perspective. UCM traffic pays off for its senders when it is noticed and consumed by Internet users; the industry is, therefore, dependent on a common-pool resource that is accessed through an information asset. An analytical model of the industry is derived and solved computationally, and two dimensions of information qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Although our instinct is to keep our email addresses private, models show that fewer spam messages would be aimed at the average inbox if all addresses were public knowledge. 6 The discussion surrounding a proposed do-not-spam registry in the U.S. is an example of this particular information effect interacting with anti-spam policy. 1…”
Section: The Surprising Effect Of Better Filtersmentioning
confidence: 98%
See 1 more Smart Citation
“…Although our instinct is to keep our email addresses private, models show that fewer spam messages would be aimed at the average inbox if all addresses were public knowledge. 6 The discussion surrounding a proposed do-not-spam registry in the U.S. is an example of this particular information effect interacting with anti-spam policy. 1…”
Section: The Surprising Effect Of Better Filtersmentioning
confidence: 98%
“…6 As filters improve, the information assets of spammers become more valuable and lead to more, not less, overall spamming activity. This is troubling to contemplate, because it means no amount of spending on better filters will be enough.…”
mentioning
confidence: 99%
“…In Plice et al (2008), it is showed that internet users consider spam 'objectionable', due to the fact that it induces direct cost (security infrastructure) and indirect cost (information overload). Spam is mainly fought by two parties ).…”
Section: Spam Economicsmentioning
confidence: 99%
“…degrading user experience 2. containing malicious software that, when is executed, could destroy the computing system 3. transferring and discovering waste a significant amount of network and computing resources [23] from user side, shows that internet users consider spam "objectionable" due to fact that it induce direct cost (security infrastructure) and indirect cost (information overload). The real financial profit of spam is aiming for the cost of sending spam against anti-spam techniques to be less than the return from the negligible response from recipients [24].…”
Section: Economic Modelingmentioning
confidence: 99%